Cost effectiveness of letrozole and purified urinary FSH in treating women with clomiphene citrate-resistant polycystic ovarian syndrome: a randomized controlled trial. (2nd January 2017) - Hassan, AbdelGany; Shehata, Nesreen; Wahba, Amr
Abstract: We aimed to compare the cost effectiveness of letrozole versus purified urinary follicle stimulating hormone (FSH) in treating patients with clomiphene citrate (CC)-resistant polycystic ovary syndrome (PCOS). This was a randomized trial conducted in Cairo University and Beni-Suef University Hospitals, Egypt. A cohort of 140 eligible women was randomized to receive either letrozole 2.5 mg twice daily for five days, or FSH using a graduated regimen starting with a dose of 75 IU. Treatment was repeated for three months if pregnancy did not occur. There were no significant differences between the two treatments in the cumulative clinical pregnancy rate (30% vs. 34%; p  = 0.578), cumulative ovulation rate (47% vs. 57%; p  = 0.236), miscarriage rate (9% vs. 4%, p  > 0.999) or multiple pregnancy rate (0% and 8%, p  = 0.491) but the FSH cycles were 4.8 times more expensive. Letrozole and FSH were both effective in treating women with CC-resistant PCOS but letrozole was more cost effective.Study registration number: NCT02304107.